Dampak Pelatihan dan Disiplin Kerja terhadap Kinerja Karyawan PT BPR - Alicia Mercy Sitompul; Dewi Fadila; Paisal Paisal (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of training and work discipline on employee performance at PT Bank Perekonomian Rakyat Sumatera Selatan (Perseroda). A quantitative approach with multiple linear regression analysis was applied, and data were obtained through questionnaires distributed to 50 employees who also represented the study population. The results indicate that both training and work discipline have a positive and significant effect on employee performance, either partially or simultaneously. Well-planned training programs enhance employees’ knowledge, technical abilities, and professionalism, enabling them to perform their duties more efficiently. Meanwhile, work discipline promotes responsibility, punctuality, adherence to company regulations, and consistency in task completion. Together, these variables explain 37.4% of the variation in employee performance, while the remaining percentage is influenced by other factors not examined in this study. The findings emphasize that structured and continuous training programs, combined with consistent discipline enforcement, play a strategic role in developing high-performing human resources. Therefore, organizations should prioritize improving employee competence and discipline to achieve optimal performance and effectively support the realization of organizational goals.